2018
DOI: 10.1037/ccp0000307
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of SecondStory, an intervention targeting posttraumatic growth, with bereaved adults.

Abstract: These findings suggest that SecondStory may not facilitate PTG more effectively than existing interventions but may be promising for addressing depression. Positive interventions may productively be refined to support people experiencing trauma and loss. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…To date, much of the research on interventions for trauma resilience has focused on adverse events that happened in the past, such as adverse childhood events, sexual assault, or wartime combat. Those studies primarily focus on the role of positive rumination about past experiences, which can lead to meaning-making and post-traumatic growth [ 35 ]. On the other hand, our findings offer insight into the impact of expressive writing on resilience during an ongoing trauma.…”
Section: Discussionmentioning
confidence: 99%
“…To date, much of the research on interventions for trauma resilience has focused on adverse events that happened in the past, such as adverse childhood events, sexual assault, or wartime combat. Those studies primarily focus on the role of positive rumination about past experiences, which can lead to meaning-making and post-traumatic growth [ 35 ]. On the other hand, our findings offer insight into the impact of expressive writing on resilience during an ongoing trauma.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the available data has not supported this view, although more longitudinal research is needed. For example, in an 8-week randomized control trial using an intervention called SecondStory, transformational processing was associated with decreased depressive symptomology but had no effect on posttraumatic growth (Roepke et al, 2018; see also Webster et al, 2018).…”
Section: Affective Behavioral and Cognitive Processes That Support Pe...mentioning
confidence: 99%
“…The model includes three constructs that are potentially modifiable through intervention (posttraumatic growth, social support, and physical activity). Posttraumatic growth enhancement is an intervention that aims to facilitate posttraumatic growth by helping individuals make meaning of the past and plan a purposeful future (Roepke et al, 2018). A systematic review of studies investigating moderators of the relationship between social support and symptoms of PTSD concluded that social support interventions may have a meaningful impact on PTSD severity (Zalta et al, 2021).…”
mentioning
confidence: 99%